Differential expression of ten-eleven translocation genes in endometrial cancers. Issue 3 (March 2017) - Ciesielski, Piotr; Jóźwiak, Paweł; Wójcik-Krowiranda, Katarzyna; Forma, Ewa; Cwonda, Łukasz; Szczepaniec, Sylwia; Bieńkiewicz, Andrzej; Bryś, Magdalena; Krześlak, Anna
Ten-eleven translocation proteins are α-ketoglutarate-dependent dioxygenases involved in the conversion of 5-methylcytosines (5-mC) to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine, and 5-carboxylcytosine that play a significant role in DNA demethylation. Deregulation of TET genes expression and changes in the level of 5-hmC are thought to be associated with the onset and progression of several types of cancer, but there are no such data related to endometrial cancer. The aim of the work was to investigate the messenger RNA expression levels of TET1, TET2, and TET3 in relation to clinicopathological characteristics of endometrial cancer as well as the correlation between expression of TET genes and the level of 5-hmC/5-mC. The prognostic significance of TETs expression for overall survival was established. We found that TET1 and TET2 messenger RNA expression was lower and TET3 was higher in cancers compared to normal tissues. Positive correlation between 5-hmC and the relative expression of TET1 and TET2 was found, but no correlation was observed in the case of TET3 . Decreased expression of TET1 and TET2 was significantly associated with increased lymph node metastasis and International Federation of Gynecology and Obstetrics stage. Kaplan–Meier analysis indicated that low TET1 expression predicted poor overall survival (p = 0.038). Multivariate analysis identified the TET1 expression in endometrial cancer as an independent prognostic factor. Our results suggest that decreased expression of TET1 correlates with tumor progression and may serve as a potential prognostic biomarker in endometrial cancer.